Cuteness and aggression in military picturebooks - Bettina Kümmerling-Meibauer; Jörg Meibauer (Problemy Wczesnej Edukacji)
As a subspecies of ideologically loaded picturebooks, this chapter focuses on military picturebooks. This term encompasses picturebooks dealing with war and the roles of soldiers. In the first part,a taxonomy of military picturebooks is created which is exemplified by telling examples. The second part focuses on a particular narrative problem of military picturebooks that is of interest to a cognitive theory of picturebooks (as pursued by Kümmerling-Meibauer & Meibauer 2013). On the one hand, it is not possible to represent war as a good thing across the board; on the other hand, war is depicted with respect to certain scenarios of self-defence. The narrative solution seems to be that “cute” characters (that is, anthropomorphic animals and vehicles) are introduced who serve as positive military protagonists that have to fight against aggressive characters representing the enemy. In military picturebooks, there is a contrast between cuteness and aggression that is astonishing when regarding the typical pedagogical demands on the accommodation of picturebooks to the child’s cognitive abilities.